Spatial Visions: Mobility and the Social Order in Pakistani Womenâ€™s English-Language Partition Fiction - Cilano, Michigan State University, USA, Cara (Asiatic: IIUM Journal of English Language and Literature, 2016)
Two fictions by Pakistani women about the â€œlong partition,â€ a concept introduced by Vazira Fazila-Yacoobali Zamindar to refer to the temporally expansive â€œpostcolonial burden of [the] political partitionâ€ of the subcontinent (3), provide unique insights into a vision of emplaced citizenship from a non-Muslim minority perspective. Bapsi Sidhwaâ€™s 1991 novel Cracking India, for instance, offers readers an opportunity to understand territories as spaces created through mobility of and interactions between Muslims and non-Muslims during the partition era. The novelâ€™s historical focus brings forth questions about how places and groups affected and were affected by the British withdrawal from the subcontinent, the violence that ensued, and the efforts to (re-) constitute place and peoples â€“ or, a social order â€“ that occurred subsequently. Similarly, Maniza Naqviâ€™s 2008 novel A Matter of Detail features toothless efforts to reclaim place through mobility so as to reanimate a belonging changed or hidden in the aftermath of partition and the development of an increasingly religiously intolerant Pakistan. While I make no claim to the unmediated representational abilities of partition fiction, I do contend that novels like Sidhwaâ€™s and Naqviâ€™s grant imaginative insights into lived experiences and possibilities, which, in turn, can motivate alternative social orders. For instance, Cracking India demonstrates the effects of the dissolution of one type of order and the struggles to establish alternatives in the newly created Pakistan. In contrast, A Matter of Detail considers the consequences of the durability of a social order when alternatives fail.